Strategi Penggunaan Spinning wheel dalam Mengenalkan Huruf Hijaiyah pada Kelompok B di TK Negeri Harmonis Kecamatan Tapa Kabupaten Bonebolango - Siti Hajar W. H. Uba; Irvin Novita Arifin; Nurhayati Tine (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the strategy of using Spinning wheel media in introducing hijaiyah letters to early childhood at TK Negeri Harmonis. The research employed a qualitative approach with a descriptive method. The subjects of this study were group B teachers and students, with data collected through observation, interviews, documentation, and triangulation to ensure data validity. The findings indicate that the Spinning wheel media effectively increases children’s enthusiasm, motivation, and concentration in recognizing hijaiyah letters. The learning process becomes more interactive since children are directly involved in the game, which is presented in an enjoyable way. Furthermore, this media helps teachers deliver materials in a more varied and engaging manner, avoiding monotonous approaches and better aligning with the developmental characteristics of early childhood. Thus, the Spinning wheel has proven to be an effective innovative learning strategy that enables children to recognize, memorize, and understand hijaiyah letters more quickly. This study emphasizes the importance of utilizing creative media to enhance the quality of early childhood education, particularly in the aspect of religious literacy.